Drawing as Therapy. (Londen : The School of Life, 2021)
When we're young, all of us draw. As we grow older, most of us stop. We come to see drawing not as a type of play, but as a craft or skill - one that we can do either well or not. But to see drawing in this way is to deny ourselves one of life's great pleasures, one with profound psychological benefits. By allowing us to express ourselves creatively, and capture our thoughts and ideas on paper, drawing can be a form of therapy. Drawing as Therapy is a collection of playful, creative prompts and exercises that introduce us to the curative powers of drawing. Divided into eight chapters, they invite us to reflect on different aspects of our life and psyche - our personality, moods, memories and passions - by attempting to render them through art. Through art, you can discover hidden byways of our minds, find new perspectives on our difficulties, summon a state of calm, and begin a process of self-recovery and healing. The exercises won't teach you how to draw. Instead, they will teach you an entirely new way of thinking about drawing, where there is no such thing as failure or success, only self-discovery and, in the best sense, play.
Keywords: Drawing therapy